1978
DOI: 10.1037/0012-1649.14.6.635
|View full text |Cite
|
Sign up to set email alerts
|

Changes in representation of body image as a function of menarcheal status.

Abstract: The significance of menarche for girls' body image and sexual identification was investigated by assessing human figure drawings produced by adolescent girls on two occasions, 6 months apart. Three groups of subjects were studied: girls who were premenarcheal on both test occasions, girls who were postmenarchealon both test occasions, and girls who changed menarcheal status between the two test administrations. Parallel results were obtained from both longitudinal and crosssectional comparisons of pre-versus p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

1986
1986
2012
2012

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 67 publications
(21 citation statements)
references
References 22 publications
0
21
0
Order By: Relevance
“…However, there was also evidence to the contrary. Koff, Rierdan, and Silverstone found that after menarche there was a reorganization of body image, that is, an increase in identification with mature femininity 23 . These investigators interpreted this finding as evidence that menarche had a positive impact on the development of identity, contrary to the view of menarche as a traumatic developmental event.…”
Section: Overview Of Past Researchmentioning
confidence: 98%
“…However, there was also evidence to the contrary. Koff, Rierdan, and Silverstone found that after menarche there was a reorganization of body image, that is, an increase in identification with mature femininity 23 . These investigators interpreted this finding as evidence that menarche had a positive impact on the development of identity, contrary to the view of menarche as a traumatic developmental event.…”
Section: Overview Of Past Researchmentioning
confidence: 98%
“…For the female adolescent, it is a sharply defined, sudden, and distinct biological event (Golub, 1992;Koff, Rierdan, & Silverstone, 1978). Menarche is also a sociocultural event that is shaped and constructed by cultural institutions such as religion, science, and media (e.g., Chandra & Chaturvedi, 1992;Laws, 1990;Paige & Paige, 1981).…”
Section: Women's Menarche Stories From a Multicultural Samplementioning
confidence: 99%
“…It is the most accurately recalled pubertal stage measured among girls (Cole 2003). Moreover, menarche is a crucial time for young girls to reconstruct body image and female identity (Koff et al 1978). Age at menarche is an important indicator of pubertal development in females (Cameron and Nagdee 1996).…”
Section: Introductionmentioning
confidence: 99%